On Literature and Critical Thinking in Postmodernity - Saldaña Sagredo, Alfredo (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In these pages I aim to locate certain cultural drifts in which theory still proves to be a critical questioning tool within the epistemic context of postmodernity. Under these conditions, literature can no longer be explained with the more traditional and orthodox aesthetic approaches; it rather becomes necessary to address its different practices in the light of a critical philosophy of culture that may guide us in such complex panorama.
Keywords: Literature; Literary Theory; Critical thinking; Postmodernity